Hadith #3882 - Jami' al-Tirmidhi - Ali bin Nasr bin 'Ali bin Nasr bin 'Ali علي بن نصر بن علي بن نصر; ibn Abbas; Ikrama عكرمة; Zm'h bin Salah زمعة بن صالح (Jami' al-Tirmidhi)
“The people used to give their gifts on ‘Aishah’s day.” She said: “So my companions gathered with Umm Salamah and they said ‘O Umm Salamah! The people give their gifts on ‘Aishah’s day, and we desire good as ‘Aishah desires, so tell the Messenger of Allah (ﷺ) to order the people to give (their gifts to) him no matter where he is.’ So Umm Salamah said that, and he turned away from her. Then he turned back to her and she repeated the words saying: ‘O Messenger of Allah! My
Grade:

Hadith #349 - Sunan Ibn Majah - al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Isa bin Yzdad عيسى بن يزداد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Waki' bin al-Jarrah وكيع بن الجراح; Zm'h bin Salah زمعة بن صالح (Sunan Ibn Majah)
“The Messenger of Allah said: ‘No one of you should bathe in open land or on a roof where he is not concealed; even if he does not see anyone, he can still be seen.'”
Grade:

Hadith #540 - Sunan Ibn Majah - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Anas ibn Malik; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Zm'h bin Salah زمعة بن صالح (Sunan Ibn Majah)
“Subhanak Allahumma wa bi hamdika, wa tabarakas- muka wa ta’ala jadduka, wa la ilaha ghayruk (Glory and praise is to You, O Allah, blessed is Your Name and exalted is Your majesty, none has the right to be worshipped but You).”
Grade:

Hadith #1083 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hrmlh bin Yahya bin حرملة بن يحيى; Zm'h bin Salah زمعة بن صالح (Sunan Ibn Majah)
“I used to hear the Prophet (ﷺ) reciting at night when I was on the roof of my house.”
Grade:

Hadith #1763 - Sunan Ibn Majah - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; ibn Abbas; Ikrama عكرمة; Muhammad bin Bashar Bindar محمد بن بشار بندار; Salma ibn al-Akwa; Zm'h bin Salah زمعة بن صالح (Sunan Ibn Majah)
the Prophet (ﷺ) told Subai’ah to get married, when her postnatal bleeding ended.
Grade:

Hadith #2009 - Sunan Ibn Majah - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; ibn Abbas; Ikrama عكرمة; Muhammad bin Bashar Bindar محمد بن بشار بندار; Zm'h bin Salah زمعة بن صالح (Sunan Ibn Majah)
“There are seventy-three degrees of usury.”
Grade:

Hadith #3543 - Sunan Ibn Majah - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; ibn Abbas; Ikrama عكرمة; Muhammad bin Bashar Bindar محمد بن بشار بندار; Zm'h bin Salah زمعة بن صالح (Sunan Ibn Majah)
the Messenger of Allah (ﷺ) said: “What you mention of glory of Allah, of Tabsih (Subhan-Allah), Tahlil (Allahu-Akbar) and Tahmid (Al-Hamdu lillah), revolves around the Throne, buzzing like bees, reminding of the one who said it. Wouldn’t any one of you like to have, or continue to have, something that reminds of him (in the presence of Allah)?'”
Grade:

Hadith #4114 - Sunan Ibn Majah - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Uthman bin Muhammad; Zm'h bin Salah زمعة بن صالح (Sunan Ibn Majah)
The Prophet (ﷺ) said: ‘”Whoever narrated a Hadith from me thinking it to be false, then he is one of the two liars.”
Grade: